The Influence Of Protean Career Attitude On Proactive Work Behavior With Passion For Work And Career Self Management As Mediator Milennial Employees Dki Jakarta Provincial Government - Ade Maya Saraswati; Dedi Purwana; Henry Eryanto (IJHCM (International Journal of Human Capital Management), 2020)
The purpose of this study is to determine and analyze the influence of protean career attitude toward proactive work behavior with passion for work and career self management as a mediators. The sample determination uses purposive sampling technique. There are 389 respondents used as the samples in this research and are analyzed using Structural Equation Model (SEM). The result from this research is that protean career attitude has a significant positive effect to proactive work behavior. Protean career attitude has a significant positive effect to the passion for work. Passion for work has a significant positive effect to proactive work behavior. Protean career attitude has a significant positive effect to career self management. Career self management has a significant positive effect to proactive work behavior. Protean career attitude has a significant effect to proactive work behavior through passion for work. Protean career attitude has a significant effect to proactive work behavior through career self management. Keywords : Proactive Work Behavior, Passion For Work, Protean Career Attitude Career Self Management.